Designing a Solar Power Plant Emergency Box for Rapid Disaster Response in Bucor Wetan Village - Sulistiyanto Sulistiyanto; Muhammad Jesen IsroAfifi; Ahmad Fulqin AlBasyi (Journal of Electrical Engineering and Computer (JEECOM), 2025)
The growing pursuit of sustainable agricultural development has driven efforts to combine renewable energy systems with Internet of Things (IoT) technology to improve efficiency and productivity in farming operations. This research focuses on the design and realization of a smart farming system powered primarily by solar energy. IoT-based sensing devices are integrated to continuously monitor parameters such as soil moisture, ambient temperature, and humidity, enabling automated irrigation management that conserves both water and energy resources. The photovoltaic (PV) module supplies stable electrical power, while collected data are transmitted to a cloud platform for remote access through a mobile interface. Experimental evaluation indicates that the proposed system decreases energy usage by approximately 35%, improves irrigation precision by 28%, and boosts crop yield by 20%. These outcomes demonstrate that the synergy between solar power and IoT technology plays a vital role in achieving sustainable agricultural systems and advancing the global objectives of energy transition and climate change mitigation.